The health of newcomers : immigration, health policy, and the case for global solidarity - Illingworth, Patricia M. L., 1954-; Parmet, Wendy E. (New York : New York University Press, 2017)
Immigration and health care are hotly debated and contentious issues. Policies that relate to both issues - to the health of newcomers - often reflect misimpressions about immigrants, and their impact on health care systems. Despite the fact that immigrants are typically younger and healthier than natives, and that many immigrants play a vital role as care-givers in their new lands, native citizens are often reluctant to extend basic health care to immigrants, choosing instead to let them suffer, to let them die prematurely, or to expedite their return to their home lands. Likewise, many nations turn against immigrants when epidemics such as Ebola strike, under the false belief that native populations can be kept well only if immigrants are kept out. In this book, Patricia Illingworth and Wendy E. Parmet demonstrate how shortsighted and dangerous it is to craft health policy on the basis of ethnocentrism and xenophobia.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2017).
Keywords: Immigrants -- Medical care; Immigrants -- Medical care -- United States; Medical policy; Medical policy -- United States; Emigration and immigration -- Government policy; United States -- Emigration and immigration -- Government policy; Right to health; Right to health -- United States; Health and Wellbeing; Social services & welfare, criminology